2012
DOI: 10.1136/jclinpath-2012-200773
|View full text |Cite
|
Sign up to set email alerts
|

Sanger sequencing in routine KRAS testing: a review of 1720 cases from a pathologist's perspective

Abstract: BackgroundSanger sequencing (SS) of PCR products is still the most frequent method to test colorectal cancer for KRAS mutations in routine practice.MethodsAn audit of SS on 1720 routine cases was carried out, taking into account age, gender, specimen type (resection vs biopsies), tumour site (primary vs metastasis), tumour stage, neoplastic cells abundance (>30% vs <30%) and fixation type (buffered formalin vs simple formalin). In a subset of 50 wild-type (WT) patients correlations between SS findings and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…A single centre longitudinal analysis (484 patients) found no difference in RAS mutation prevalence between genders [25]. Another single centre analysis (1691 tumour samples) did not find a significant association between KRAS mutation rate and gender, although significant differences were observed for tumour sample site, neoplastic cell percentage and tumour stage [29].…”
Section: Discussionmentioning
confidence: 96%
“…A single centre longitudinal analysis (484 patients) found no difference in RAS mutation prevalence between genders [25]. Another single centre analysis (1691 tumour samples) did not find a significant association between KRAS mutation rate and gender, although significant differences were observed for tumour sample site, neoplastic cell percentage and tumour stage [29].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the use of different cytological methods do not affect DNA or RNA quality and molecular testing, which was confirmed by studies involving both liquid-based cytology and conventional cytological techniques [27,28,29]. The undoubted quality of cytological preparations needs to be validated by larger cytological series [18,26,30,31], which are quite scant apart from few studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These represent the vast majority of specimens analysed in the routine setting. In fact, in a recent review of 578 cases referred to our laboratory, we found that 528 (91.3%) specimens contained more than 30% of neoplastic cells 61. Besides the percentage of neoplastic cells, the limit of detection (LOD) of this technique partly depends on the specific mutation and on the experience of the person interpreting the data 62.…”
Section: The Methodsmentioning
confidence: 99%